2015
DOI: 10.1212/wnl.0000000000001997
|View full text |Cite
|
Sign up to set email alerts
|

A geographical cluster of progressive supranuclear palsy in northern France

Abstract: Objective: To describe a cluster of progressive supranuclear palsy (PSP) in northern France.PSP has not been reported in geographical, temporal, or occupational clusters. A unit of Neurology and Neurogeriatrics opened in 2005 at the Centre Hospitalier de Wattrelos, serving the population of Wattrelos and Leers (combined population 51,551) and parts of neighboring towns. For most of the 20th century, this area was a center for chromate and phosphate ore processing, textile dyeing, and tanning. Significant indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…However, it is possible that statistical differences were not found because of the overall low frequency of these jobs in our cohort. In fact, a recent report of a cluster of PSP patients in France in a geographical area with severe environmental contamination by industrial metals supports our findings …”
Section: Discussionsupporting
confidence: 92%
“…However, it is possible that statistical differences were not found because of the overall low frequency of these jobs in our cohort. In fact, a recent report of a cluster of PSP patients in France in a geographical area with severe environmental contamination by industrial metals supports our findings …”
Section: Discussionsupporting
confidence: 92%
“…The authors found no significant results because of the low precision of the Matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry (MALDI‐TOF) technology used. Regarding PSP, the cohorts of postmortem brains described in the literature are relatively small because of the low prevalence of the disease, which is approximately 5 to 6 cases per 100,000 persons . Indeed, larger cohorts are actually clinicopathological descriptions of as many as 100 cases in multicentric studies .…”
Section: Discussionmentioning
confidence: 99%
“…A cluster of PSP cases in an industrial city in France and a multicenter case-control study suggest that environmental risk factors influence PSP incidence. 7,8 …”
Section: Introductionmentioning
confidence: 99%